EPISTEMOLOGI DAKWAH FARDIYAH DALAM PERSPEKTIF KOMUNIKASI ANTAR PRIBADI - Abdul Basit (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2007)
Da ’wa fardiycih is one of the common activities in Islamic preaching and has been applied since earlier period of Islam. However, it has not applied scientific development so that it goes naturally. Referring to this case, this paper tries to discuss the epistemology of da ’wa fardiyah. The study on essence of da ’wa fardiyah will be started from the use of the term itself Since the term is not specifically found in the Quran, its definition is taken from interpersonal communication. The writer try to build a derived definition as follow: Da’wa fardiyah is face to face interaction between one individual and the other or between an individual and small group of people in order to change the individual or small group of people to live in the way of Islamic teachings. How to develop relation is applied gradually. It started from developing positive perception to mad’u and followed with developing cultural and social relation. The third phase is applied through a closed relation con- sidering potentials and differences in every individual.